The Concept of the Enlightenment. - Pinkoski, Nathan (Modern Age)
This article reviews J. C. D. Clark’s book *The Enlightenment: An Idea and Its History*, which challenges the conventional understanding of the Enlightenment as a coherent seventeenth- and eighteenth-century intellectual movement. Clark argues that the term "Enlightenment" was not used contemporaneously to denote a unified movement but was retrospectively constructed, often for political purposes such as legitimizing the French Revolution or opposing fascism. He emphasizes the theological and political contexts of key thinkers, suggesting that what is often seen as secular Enlightenment thought was deeply intertwined with religious dissent and anti-monarchical agendas. Clark’s work critiques modernist narratives that separate Enlightenment ideas from theology, proposing instead that political theology remains central to understanding the period and its legacy.